Billy the Kid returns - Kane, Joseph, 1894-1975; Natteford, Jack, 1894-1970; Rogers, Roy, 1911-1998; Burnette, Smiley, 1911-1967; Republic Pictures Corporation; Cinetel Films ([Los Angeles, CA] : Republic Pictures, 1938)
Roy Rogers plays a duel role in this western portraying Billy the Kid and also himself, who is identical in appearance to Billy. After Billy the Kid is gunned down by Pat Garrett, Rogers appears in town and causes some confusion due to his likeness to the outlaw. After a series of misunderstandings due to the mistaken identity, Rogers is able to redeem himself by bringing some criminals to justice.
Originally released as a motion picture in 1938.
Roy Rogers, Smiley Burnette, Mary Hart.
Cinematographer, Ernest Miller; editor, Lester orlebeck; music, William Lava ; musical director, Cy Feuer.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 8, 2016).
Keywords: Billy, -- the Kid -- Drama; Mistaken identity -- Drama; Outlaws -- Southwest, New -- Drama; Frontier and pioneer life -- Southwest, New -- Drama; Southwest, New -- Drama; Feature films; Western films; Internet videos; Streaming video